THE EFFECT OF THE COMBINATION OF BRANDT DAROFF PHYSICAL THERAPY AND CLASSICAL MUSIC THERAPY ON REDUCING THE LEVEL OF VERTIGO SYMPTOMS IN PUSKESMAS SUKOWONO, KABUPATEN JEMBER - Ariyantika, Dinda; Poltekkes, Rudi Hamarno; Sepdianto, Tri Cahyo; Hidayah, Nurul (Jurnal Keperawatan Terapan, 2023)
Vertigo is a disease that is very often found in the community, which is described by feeling dizzy, giddiness and unsteadiness. One of the actions that can be taken in reducing the level of vertigo symptoms is giving Brandt Daroff physical therapy and classical music therapy. The purpose of the study is to determine the effect of Brandt Daroff's physical therapy and classical music therapy on reducing the level of vertigo symptoms. The research method used was Pre Experimental Design with Intact – Group Comparison design. The respondents of this study were patients with vertigo. The participants of the study were determined using purposive sampling. The number of sample in this study were 30 people, which were divided into 15 people in the control group and 15 people in the treatment group. The results of the Independent T - Test statistical test obtained the value of Sig. (2 – tailed) p – value = 0.011 (p < 0.05) which means that there is an effect of giving Brandt Daroff physical therapy and classical music therapy in reducing the level of vertigo symptoms. Suggestions for further researchers are to pay more attention to other factors that can affect the level of vertigo symptoms. Suggestions for health workers in the future, this theory can be applied and taught to vertigo patients to reduce the level of vertigo symptoms.